Land Capability for Agriculture, Hermel District, Lebanon. Issue 2 (3rd July 2019) - Abou-Najem, Sandra; Palacios-Rodríguez, Guillermo; Darwish, Talal; Faour, Ghaleb; Kattar, Salim; Clavero Rumbao, Inmaculada; Navarro-Cerrillo, Rafael Mª
ABSTRACT: For the purpose of mapping land capability by United States Department of Agriculture (USDA) criteria, this paper presents a validated model to map land capability at a scale of 1:20, 000 using a digital elevation model and the available soil information for Hermel District (525.6 km 2 ) in Lebanon. The model was validated through fieldwork and it indicates a good overall accuracy of 89% and the significance of the model for mapping land capability at a district level. The study shows that 11.5 km 2 (2.2%), 284.6 km 2 (54.2%), 66.8 km 2 (12.7%), 147.9 km 2 (28.1%) and 14.9 km 2 (2.8%) of the region were categorized in I, II, III, IV, and V land classes respectively. The comparison between the zoning map already produced for Hermel city and the land capability map demonstrates that the land use patterns need to be modified according to identified land capability classes to sustain the remaining productive lands for future generations.